The prevalence, incidence, and admission rate of diagnosed schizophrenia spectrum disorders in Korea, 2008-2017: A nationwide population-based study using claims big data analysis. - Yoon-Sun Jung (Public Library of Science (PLoS), 2021)
This study estimated the prevalence and incidence rate of schizophrenia, schizotypal, and delusional disorders (SSDD) in Korea from 2008 to 2017 and analyzed the hospital admission rate, re-admission rate, and hospitalization period. It used the Korean nationwide National Health Insurance Service claims database. SSDD patients who had at least one visit to Korea's primary, secondary, or tertiary referral hospitals with a diagnosis of SSDD, according to the International Classification of Diseases, 10th Revision (ICD-10), were identified as SSDD cases if coded as F20-F29. Data were analyzed using frequency statistics. Results showed that the 12-month prevalence rate of SSDD increased steadily from 0.40% in 2008 to 0.45% in 2017. Analysis of the three-year cumulative prevalence rate of SSDD showed an increase from 0.51% in 2011 to 0.54% in 2017. In 2017, the five-year cumulative prevalence rate was 0.61%, and the 10-year cumulative prevalence rate was 0.75%. The hospital admission rate among SSDD patients decreased from 2008 (30.04%) to 2017 (28.53%). The incidence of SSDD was 0.05% and no yearly change was observed. The proportion of SSDD inpatients whose first hospital visit resulted in immediate hospitalization was 22.4% in 2017. Epidemiological indicators such as prevalence, incidence, and hospitalization rate play an important role in planning social and financial resource allocation. Therefore, efforts to produce more accurate epidemiological indicators are very important and this study's findings could have a significant social impact.